2019
DOI: 10.1097/01.hs9.0000567404.64167.17
|View full text |Cite
|
Sign up to set email alerts
|

Pb2232 the Natural Anticoagulants in Patients With Philadelphia‐negative Myeloproliferative Neoplasms

Abstract: Background:Myeloproliferative neoplasms (MPNs) are characterized by an increased frequency of thrombotic complications. Patients with MPNs show little or no abnormalities in traditional coagulation tests. Chronic inflammation associated with pathological secretion of several inflammatory cytokines leads to activation of endothelial cells and imbalance between coagulation and anticoagulation systems.Aims:To estimate the natural anticoagulants activity and activated protein C resistance in MPNs patients.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…studies did not enumerate the specific number of ET and PV patients. 11,12 In the TGA studies, there was a trend toward higher peak heights and shorter lag times among nonspecified MPN patients versus controls, suggestive of hypercoagulability in MPNs regardless of any treatment received. Only two studies reported the thrombosis status/incidence of their cohorts.…”
Section: Is Tga Different In Mpn Versus Controls?mentioning
confidence: 97%
See 4 more Smart Citations
“…studies did not enumerate the specific number of ET and PV patients. 11,12 In the TGA studies, there was a trend toward higher peak heights and shorter lag times among nonspecified MPN patients versus controls, suggestive of hypercoagulability in MPNs regardless of any treatment received. Only two studies reported the thrombosis status/incidence of their cohorts.…”
Section: Is Tga Different In Mpn Versus Controls?mentioning
confidence: 97%
“…There were 3 studies that combined PV, ET, and PMF patients in their analysis of TGA parameters but did not provide individual disease data (►Table 1). [11][12][13] The number of participants in each study ranged from 25 to 212 including the controls. There were six (18.8%) studies that did not have healthy controls.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations